Central Venous Catheter bundle: professional knowledge and behavior in adult Intensive Care Units - Costa, Camila Adriana Barbosa; Araújo, Fernanda Lopes; Costa, Anna Caroline Leite; Corrêa, Allana dos Reis; Kusahara, Denise Miyuki; Manzo, Bruna Figueiredo (Revista da Escola de Enfermagem da USP, 2020)
Objective To evaluate knowledge and behavior of professionals in Intensive Care Units regarding the actions recommended in the bundle on preventing central venous catheter-related bloodstream infection. Method Cross-sectional descriptive quantitative study, conducted in three Intensive Care Units. The data were collected through a face-to-face questionnaire applied to health professionals. The software R 3.3.1 was used for data analysis. Results Two-hundred and ninety-two professionals participated. Regarding knowledge, the hand hygiene item presented a higher level both for the insertion (92.46%) and maintenance (97.27%) moments. Usage of chlorhexidine as an antiseptic, followed by alcohol (47.94%) and providing a date for hub or connectors (19.87%) were the least known items. As for behavior, the professionals reported: using always the correct attire for catheter insertion (84.25%), never waiting for the antiseptic to dry before catheter insertion (25.34%) and never cleaning hub or connectors with 70% alcohol (23.86%). Conclusion Results show that the professionals’ knowledge and behavior regarding the central venous catheter bundle present deficiencies, revealing the importance of promoting training programs for this knowledge domain.